The profitability of following analyst recommendations on the Polish stock market - Adam Zaremba; Przemysław Konieczka (e-Finanse: Financial Internet Quarterly, 2015)
The profitability of analysts' recommendations is documented in numerous studies from all over the world. However, the evidence from the Polish market is relatively modest. The primary aim of this study is to fill this gap. The paper contributes to the economic literature in four ways. First, it provides fresh out-of-sample evidence on return patterns following analysts' recommendations from Poland. Second, it examines the relations between these patterns and the size of the rated companies. Finally, it investigates whether it is possible to design profitable strategies based on the discovered patterns. We use monthly stock level data from Poland and the sample period is 2004 - 2013. In order to examine the profitability of analysts' reports, we build market-neutral portfolios and test their performance against CAPM, Fama-French three-factor and Carhart fourfactor models. The principal findings can be summarized as follows. First, we document that the top rated companies deliver better returns than the bottom rated companies. Second, we find that the profitability is particularly impressive among the small companies. Third, the abnormal returns are partially explained by momentum and value based factors. Finally, we provide evidence that strategies based on information in recommendations deliver statistically significant positive abnormal rates of return.
Keywords: G11; G12; 330; stock market; stock recommendations; analysts; Warsaw Stock Exchange